SERBUK JAHE, CENGKEH, DAN KAYU MANIS GUNA ATASI DEPRESI PADA KESEHATAN MENTAL - Anggraini, Devina Ingrid; Setiawan, Iwan (SWAGATI : Journal of Community Service, 2023)
Mental health is a condition when an individual does not experience feelings of guilt about himself, and has a realistic estimate of himself and can accept his own shortcomings or weaknesses, has the ability to face the problems that exist in his life, has satisfaction in his social life, and have happiness in life. There are several problems due to the pandemic, one of them is related to education, school dropped out. Based on the results of an interview with the Head of Youth Organization in Ngombakan Village, Sukoharjo, the rate on teenagers who dropped out of school were informed that from 10 teenagers, 6 of them did not continue their education and chose to work for money, 2 of them did not continue their Japanese language school due to the effects of the COVID-19 pandemic, and 2 of them did not continue their studies because they were lazy to think. The purpose of this community service activity was to treat depression in an effort to improve teenagers quality of life, provide education about how to use natural materials to help overcome depression, and gave training on making "SERJA CENGKANIS" (Serbuk Jahe Kombinasi Cengkeh dan Kayu Manis) Ginger Powder Combination of Cloves and Cinnamon. The results of the activity evaluation show that all the criteria and indicators success of the activity have been achieved. Targets and goals achieved up to 58%. The level of community knowledge on the pre-test value, which is 87, increases during the post-test, which is 90. The level of community satisfaction with the implementation of activities reaches 94%.